The Impact of Dividends’ Policy on the Cost of Equity of Enea S.A. - Wrycol, Anna (Journal of Finance and Financial Law, 2015)
The article is an attempt to depict the procedures and regulations accompanying the policy of dividends in a company with a particular emphasis which is put on Enea S.A. The purpose of the empirical part is to analyze and assess the effectiveness of applying discounted dividends model to calculate the cost of equity for the company. It juxtaposes advantages and impediments in using the model, as well as infers if Gordon model is adequate in estimating the cost of equity for the presented company.